Numerical analysis of deflections of multi-layered beams = Numeryczna analiza ugięć belek warstwowych - Biliński, Tadeusz (1932- ); Socha, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper concerns the rheological bending problem of wooden beams reinforced with embedded composite bars. A theoretical model of the behaviour of a multi-layered beam is presented. The component materials of this beam are described with equations for the linear viscoelastic five-parameter rheological model. Two numerical analysis methods for the long-term response of wood structures are presented. The first method has been developed with SCILAB software.
Keywords: ABAQUS; drewno; kompozyt; konstrukcje warstwowe; MES; pełzanie; reologia; wzmacnianie; wood; composite; composite construction; rheology; creep; strengthening